PENGARUH KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVEING PADA CAFÉ AZALEA DI SITUBONDO - Wardhani, Alivia Riskiyana; Kusnadi, Edy; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2022)
Marketing is a social and executive process in which individuals and groups obtain what they need and want through creating, offering and exchanging products of value with others. The purpose of this study was to analyze and examine the effect of Service quality and Price perception in determining Consumer loyalty with Consumer satisfaction as an intervening variable. The population in this study are consumers of Café Azalea in Situbondo. Sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study using the structural equation model – partial least square (PLS-SEM). The results of the direct influence hypothesis test using the smart PLS 3.0 application, show that Service quality has a significant positive effect on Customer satisfaction, Price perception has a significant positive effect on Consumer satisfaction, Service quality has a significant positive effect on Consumer loyalty, Price perception has a significant positive effect on Consumer loyalty, Consumer satisfaction has a significant positive effect on Consumer loyalty. The results of the indirect influence hypothesis show that the Service quality variable on Consumer loyalty through Customer satisfaction has a significant positive effect, Price perception on Consumer loyalty through Customer satisfaction has a significant positive effect.